CircRNA circ_0000190 inhibits the progression of multiple myeloma through modulating miR-767-5p/MAPK4 pathway - Feng, Yashu (J Exp Clin Cancer Res, 2019)
BACKGROUND: Multiple myeloma (MM) accounts for 10% of all hematological malignancies. Dysregulation of microRNAs (miRNAs) or long non-coding RNAs (lncRNAs) has important impacts on progression of MM. Circular RNAs (circRNAs) are correlated with malignancy in the modulation of tumor progression. This study aims to investigate the effect of circ_0000190 on regulating the progression of MM. METHOD: Microscopic examination via single molecule fluorescent in situ hybridization indicates the location of circ_0000190. qRT-PCR and Western blot were used to evaluate the expression of RNAs and proteins. Potential target of circ_0000190 was searched as miRNA, and examined by luciferase reporter assay. A computational screen was also conducted to search the potential target of miRNA. In vitro cell viability, proliferation, apoptosis assays and flow cytometric were performed to assess the effects of circ_0000190 and its target on MM. Mice model of human MM was established with subcutaneous xenograft tumor, qRT-PCR and western blot were performed to detect the underlying mechanisms of circ_0000190 on MM. RESULTS: Circ_0000190 was located in the cytoplasm, and down-regulated in both bone marrow tissue and peripheral blood, while the target of circ_0000190, miR-767-5p, was up-regulated, suggesting a negative correlation between them. The binding ability between circ_0000190 and miR-767-5p was confirmed by luciferase reporter assay. Moreover, circ_0000190 inhibited cell viability, proliferation and induced apoptosis of MM thus inhibiting cell progression, which is partially through the negative regulation of miR-767-5p. Mitogen-activated protein kinase 4 (MAPK4) is a direct target of miR-767-5p. In addition, over-expression of miR-767-5p promoted cell progression by directly targeting and regulating MAPK4. The MM model mice with administration of circ_0000190 suppressed tumor growth and progression. CONCLUSION: Our results revealed that the ability of circ_0000190 to protect against MM was inherited through repression of miR-767-5p, and miR-767-5p might be a tumor drive through targeting MAPK4. Therefore, a novel role of circ_0000190 on regulating the progression of MM was found, and the clinical application of circRNAs might represent a strategy in MM. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13046-019-1071-9) contains supplementary material, which is available to authorized users.